KEMITRASEJAJARAN PRIA-WANITA DALAM ISLAM SEBAGAI KRITIK WACANA PATRIARKIS DAN TEOLOGI FEMINISME - Hurnawijaya - Hurnawijaya (Hukum Keluarga Islam, 2024)
Abstract Patriarchy is a system that places adult men in the central or most important position, while others such as wives and children are positioned according to the interests of the patriarch (adult men). In a patriarchal system, women are positioned as wives who are tasked with accompanying, complementing, entertaining and serving their husbands (the patriarch), while children are positioned as the next generation and entertainers of their fathers. This system influences the interpretation and understanding of religion, in this case Islamic teachings. Interpreting religion with a patriarchal lens can give birth to a patriarchal culture that positions women as always and always under men and men must always and always be above women, namely in a position to lead, regulate and control, regardless of whether the man is capable. and fulfill the requirements or not. This understanding then received deconstruction from the feminist movement which challenged interpretations and understandings that tended to be patriarchal, such as the theological construction carried out by several Muslim figures such as Riffat Hassan, Ameena Wadud and so on to realize gender equality, unfortunately the theological construction of gender equality built by Riffat Hassan for example, simply adopting the concept of feminist theology that developed in the West. Even though it is different from women in the West, which has a dark history because women are seen as despised and treated discriminatorily, in Islam women are actually glorified. The arrival of Islam has eliminated jahiliyah customs that were detrimental to women and raised their dignity. If the subordination of women in the West gets legitimacy from the Bible, in the Koran women are actually glorified. Therefore, a new understanding of religion is needed using a gender justice perspective that relations in Islam are not like the understanding in patriarchal culture or gender equality as advocated by western feminism but rather gender harmony in the form of equal partnerships between men and women. Keywords: Interpretation, Gender, Patriarchy, Feminism, Equal Partnerships